Education piety: special reference to Abu Hamid al- Ghazali and Abdul Rahman Ibn Khaldun - Bensaid, Benaouda; Machouche, Salah (IGI Global, 2020)
This chapter seeks to explore the crossroads between learning in Islam and spirituality, and also the methods according to which Muslim instructors shape students’ experiences in a context of piety development. This study also examines questions pertaining to the concept of spirituality in education, methods pedagogic principles that further merge spiritual discipline with knowledge acquisition. The theoretical research draws on the textual analysis of early works of Muslim scholars, more specifically on Abdul Ibn Khaldun and Abu Hamid al-Ghazali, given their prominent positions in the history of Muslim education. This study shows that the Islamic learning has always taken students’ spiritual growth for granted and has, despite differences of practices across Muslim regions, always maintained the refining of learners’ spiritual character.